Dimensi-Dimensi Fiqh dan Aliran-Aliran Mazhab dalam Islam: Pendekatan Konseptual, Historis, dan Analitis - Roslan; Ariyanti Alwan; Mustamin Giling (Al-Kindi, 2026)
Fiqh, as the result of human ijtihad in understanding Islamic law, possesses complex dimensions and diverse schools of thought. This article comprehensively discusses the dimensions of fiqh, encompassing normative, social, philosophical, and historical aspects, and analyzes the schools of fiqh that developed within the Sunni (Hanafi, Maliki, Shafi'i, Hanbali) and Shia (Ja'fari) traditions. Through a qualitative approach based on literature review with historical, normative, and philosophical perspectives, this article finds that differences in legal istinbath methodology between schools of thought, influenced by geographical and social factors, and differing understandings of texts, are actually a blessing that enriches the intellectual treasury of Islam. The relevance of the plurality of schools of thought in the contemporary era lies in their flexibility in responding to the dynamics of modern society and the concept of moderation within schools of thought as a middle ground between narrow fanaticism and excessive liberalism